Clinical predictors of wheeze trajectories and associations with allergy in Asian children - Lau, Hui Xing (2024)
Background: Childhood wheezing is a highly heterogeneous condition with an incomplete understanding of the characteristics of wheeze trajectories, particularly for persistent wheeze. Objective: To characterize predictors and allergic comorbidities of distinct wheeze trajectories in a multiethnic Asian cohort. Methods: A total of 974 mother-child pairs from the prospective Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort were included in this study. Wheeze and allergic comorbidities in the first 8 years of life were assessed using the modified International Study of Asthma and Allergies in Childhood questionnaires and skin prick tests. Group-based trajectory modeling was used to derive wheeze trajectories and regression was used to assess associations with predictive risk factors and allergic comorbidities. Results: There were 4 wheeze trajectories derived, including the following: (1) early-onset with rapid remission from age 3 years (4.5%); (2) late-onset peaking at age 3 years and rapidly remitting from 4 years (8.1%); (3) persistent with a steady increase to age 5 years and high wheeze occurrence until 8 years (4.0%); and (4) no or low wheeze (83.4%). Early-onset wheezing was associated with respiratory infections during infancy and linked to subsequent nonallergic rhinitis throughout childhood. Late-onset and persistent wheeze shared similar origins characterized by parent-reported viral infections in later childhood. However, persistent wheezing was generally more strongly associated with a family history of allergy, parent-reported viral infections in later childhood, and allergic comorbidities as compared with late-onset wheezing. Conclusion: The timing of viral infection occurrence may determine the type of wheeze trajectory development in children. Children with a family history of allergy and viral infections in early life may be predisposed to persistent wheeze development and the associated comorbidities of early allergic sensitization and eczema.